Lower-body strength, power and flexibility in karateka: implications for musculoskeletal health - Shaw, I.; Schwartzel, D.; Millard, L.; Breukelman, G. J.; Shaw, B. S. (Archives of Budo, 2020)
Background and Study Aim: Karate training has a long history of improving general health and wellbeing, however, little or no research has been undertaken to determine the effect of karate training on muscular fitness, lower-body strength, power and flexibility. The aim of this study was to enhance the knowledge about lower-body strength, power and flexibility of karate athletes of different levels of training and not trainees.